2009
DOI: 10.1136/emj.2008.062281
|View full text |Cite
|
Sign up to set email alerts
|

Syncope management in the UK and Republic of Ireland

Abstract: The ED management of syncope patients in the UK and Republic of Ireland is varied. Only 18% of ED have specific guidelines for managing this difficult condition and only 18% have access to a specialist syncope clinic. A robust consensus UK syncope guideline is clearly required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Here we have extended these observations to a broad group of patients presenting with syncope and have demonstrated that it is the single most powerful predictor of adverse outcome, particularly death. Although in the United Kingdom only 5% of EDs currently have point-of-care BNP testing (25), 44% have point-ofcare testing facilities (25) and almost all have rapid access to laboratory BNP, because of National Institute of Health and Clinical Excellence recommendations (26).…”
Section: Discussionmentioning
confidence: 99%
“…Here we have extended these observations to a broad group of patients presenting with syncope and have demonstrated that it is the single most powerful predictor of adverse outcome, particularly death. Although in the United Kingdom only 5% of EDs currently have point-of-care BNP testing (25), 44% have point-ofcare testing facilities (25) and almost all have rapid access to laboratory BNP, because of National Institute of Health and Clinical Excellence recommendations (26).…”
Section: Discussionmentioning
confidence: 99%
“…The management of syncope in the emergency department varies greatly among physicians and centres, 37 although several evidencebased recommendations have been published in recent years. [38][39][40] Therefore, the population of patients without an evident cause of syncope may vary considerably according to the practices of local emergency departments, and judgment for generalization of the San Francisco Syncope Rule in this population remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The current use of observation wards and syncope clinical decision units is not widespread; for example only 27% of UK EDs have an observation ward that admits syncope patients. [18] The new ESC syncope guidelines promote the use of syncope clinical decision units within the ED. They allow a period of ECG monitoring for patients thought to be at risk of arrhythmic syncope and selected echocardiography if structural or valvular heart disease, or heart failure, is suspected.…”
Section: Should My Hospital Have a Syncope Clinical Decision Unit?mentioning
confidence: 99%
“…The current use of specialist syncope outpatient clinic is also not widespread; for example only 18% of UK EDs have access to a specialist syncope outpatient clinic. [18] The new ESC syncope guidelines promote the use of rapid access syncope clinics as a safe way to reduce admissions and ensure patients receive timely, focused expert opinion and investigation. Setting up a syncope rapid access syncope clinic in your hospital requires a multidisciplinary team approach, including emergency medicine, acute medicine, care of the elderly, neurology, cardiology, electrophysiology, nursing, cardiac imaging and neurophysiology, keen enthusiasts (a syncope site champion) and a lot of energy.…”
Section: Should My Hospital Have a Syncope Clinical Decision Unit?mentioning
confidence: 99%